DESKRIPSI FORMALIN PADA APEL DAN ANGGUR IMPORT DI KIOS BUAH DI EX KOTATIF PURWOKERTO KABUPATEN BANYUMAS TAHUN 2014 - Tri Widya Ningrum; Lagiono Lagiono (Poltekkes Kemenkes Semarang, 2015)
Food is every biological, animalistic, processed or unprocessed for human drinking and feedingconsumption including food additive feeding material and other material for savingprocess, or drinking. Formalin is chemical efficient substance but, forbid to food additive, generallyformalin used in textile industry to avoid textile tangled. The goal of this research to known fruit quality(organoleptic) fruit peel, fruit color and fruit flavors in general and to know thereis or now formalin incontamination in import apples and grapes sold at ex kotatif Purwokerto market.This Resecearher of observation method description it was mean to descript import appes andgrapes quality(organoleptic) generally and to know containing formalin at apples and grapes sold in exkotatif Purwokerto year of 2014.Labratorium examining in samples from import apples and grapes, the sample containing formalinpositive were 11 sample those are American grape was 0,218 ppm, Apples Red Delicious code B 1,406ppm, American grape, Apple Red Delicious Code C was 2,463 ppm, Australion grape was 0,167 ppm,Apple Fuji was 2,063 ppm, Apple Red Delicious was 2,049ppm ( Code D), Apple Fuji was 4,73 ppm,Australion grape was 0,204 ppm, Apples Red Delicious was 5,011 ppm ( Code E). And others fruit(Apple and Grape) was not formalin containing.Generally in apple import Fuji, RD, and GS and grape import Australion and American for sample 5all of them was good. So it is resecearher recommence to apply from health department safety foodquality and food nutrition come to Purwokerto town is like explained in government regulation number28th 2004.